2021
DOI: 10.1101/2021.03.29.437513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conjugative plasmid transfer is limited by prophages but can be overcome by high conjugation rates

Abstract: Antibiotic resistance spread via plasmids is a serious threat to successful treatment and makes understanding plasmid transfer in nature crucial to preventing the global rise of antibiotic resistance. However, plasmid dynamics have so far neglected one omnipresent factor: active prophages (phages that are integrated into the bacterial genome), whose activation can kill co-occurring bacteria. To investigate how prophages influence the spread of a multi-drug resistant plasmid, we combined experiments and mathema… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Harrison et al [51] showed recurrent selective sweeps of phage resistance mutations can initially stabilise costly plasmids, but ultimately drove the loss of plasmids from populations of Pseudomonas fluorescens [51] . Similar results have been observed during prophage infection, where plasmid spread is limited due to an increased mortality rate in the plasmid carrying fraction of the population [52] . Some phages can also specifically target the conjugation machinery of plasmids, selecting against plasmid carriage resulting in the loss of the plasmid and hence the phage receptor, as a mechanism of phage resistance [53] .…”
Section: Factors Limiting Plasmid Transfer and Persistence Within Mic...supporting
confidence: 84%
See 1 more Smart Citation
“…Harrison et al [51] showed recurrent selective sweeps of phage resistance mutations can initially stabilise costly plasmids, but ultimately drove the loss of plasmids from populations of Pseudomonas fluorescens [51] . Similar results have been observed during prophage infection, where plasmid spread is limited due to an increased mortality rate in the plasmid carrying fraction of the population [52] . Some phages can also specifically target the conjugation machinery of plasmids, selecting against plasmid carriage resulting in the loss of the plasmid and hence the phage receptor, as a mechanism of phage resistance [53] .…”
Section: Factors Limiting Plasmid Transfer and Persistence Within Mic...supporting
confidence: 84%
“…The complexity of microbial communities will make it challenging to answer such questions, in part due to the diversity of hosts — differing in their ability to receive, maintain and disseminate plasmids — as well as the diversity of interspecies and multitrophic interactions that are present within natural communities. A combination of approaches including the use of more representative in vitro multispecies and multitrophic communities (such as 54 , 56 ), increased focus on theoretically modelling the effects of diversity and interspecies interactions (such as 52 , 65•• ), and observing the dynamics of plasmid transfer within natural microbiomes (such as [24] ) will all contribute to developing a deeper understanding of plasmid dynamics in complex communities.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicts and collaborations between MGEs also extend across MGE types. In a series of experiments extended and explored with deterministic modelling, Igler et al [43] investigate how conjugative plasmids and integrative prophages affect each other's transmission. Though neither the plasmid nor the phage used in their experiments (lambda and RP4) contained systems known to directly interfere with transfer, they found that prophages limited conjugative plasmid spread directly by killing recipients, and suggest that prophages may also inhibit plasmid entry.…”
Section: Mges In An Mge Worldmentioning
confidence: 99%
“…Data accessibility. Data are available from the Dryad Digital Repository: https://doi.org/10.5061/dryad.s4mw6m972 [52]. Competing interests.…”
Section: Authorsmentioning
confidence: 99%